Tunneling spectroscopy into YBa2Cu4O8: Intralayer and interlayer analysis. - Cucolo, A; Leo, R; Romano, P; Dabrowski, B; Hinks, D; Radaelli, P (1994)
We have measured the superconducting and normal tunneling characteristics of quality controlled planar junctions based on YBa2Cu4O8 (Y124) single crystals. Our data show that the in-plane properties are similar to the YBa2Cu3O7 (Y123) system. A higher value of the zero-bias conductance is measured in the Y124, indicating an increased number of normal electrons due to the presence of the double chain structure. Linearity of the background conductance is observed in both compounds. Less steep slopes are found in Y124 that might indicate a reduced interlayer coupling in this system. © 1994 The American Physical Society.